Alteraciones tiroideas en pacientes con diabetes mellitus tipo 2: prevalencia y factores de riesgo asociados. Revisión sistemática - Tenepaguay Rivera, Jhosselin Anahi (2023)
The function of the thyroid gland is to produce the necessary amount of thyroid hormones such as thyroxine (T4), triiodothyronine (T3) and thyrotropin (TSH), which are involved in growth, maintenance of most body functions and regulation of metabolism. There are risk factors that increase the likelihood that a person with type 2 diabetes mellitus (DM2) will develop thyroid disease. Thyroid disorders in patients with DM2 can have a negative impact on health due to the complications they produce, especially when there is no timely diagnosis. To address these problems, a systematic review was conducted to establish the prevalence of thyroid disorders, the associated risk factors and the main thyroid disorders in patients with DM2. In this review, 19 articles were analyzed, where the prevalence of thyroid disorders was approximately 23.79%. The main alterations found in patients with DM2 were: hypothyroidism, with a frequency of 19.94%; followed by subclinical hypothyroidism, with 13.2%; and approximately 13.04% presented autoimmune thyroid disease, also the risk factors that presented association before the presence of thyroid alterations in patients with DM2 were: female sex, patients older than 48 years, increased BMI, hypertension, glycosylated hemoglobin, dyslipidemia and poorly controlled glycemic control